Nasal Hump Reduction may Improve Dorsal Nasal (Rintala) Flap - Javad Rahmati; Zahra Farahani-nik; Hojjat , Molaei-Govarchin-Qala (Journal of Ardabil University of Medical Sciences, 2020)
Introduction: Skin defect reconstruction following tumor resection, is a challenge for surgeons. Nose as a key point of aesthetics has a significant role in this scenario. One of the practical approaches is dorsal nasal flap (Rintala) to cover lower 1/3 nasal defects. The disadvantages of this method are limitation to reach lower areas, especially nose tip, flap ischemia and wound dehiscence. Case report: A 47 years old man with supratip BCC lesion underwent tumor resection and prepared for dorsal nasal flap reconstructive surgery, in which dorsal hump resection caused relaxed flap transfer and ultimately more acceptable profile view. Conclusion: Advancement of the dorsal nasal flap more distally can be achieved by dorsal hump reduction in selected patients, which makes patients more satisfied with their new nasal form and appearance and reduces the risk of distal flap ischemia.